Synthesis and Characterization of a Reversible and Tunable Smart Polymer - Lindberg, Charles; Conor, Philip; Shoulak, Brianna; Stubbs, Elizabeth; Laskowski, Elizabeth; Glogowski, Elizabeth M. (My University, 2017)
Polymers are made of covalently bonded repeat units, called monomers, which make up long chains. The structure can be controlled to achieve a diblock copolymer with two different repeat units connected in blocks. “Smart” polymers are polymers that can change their properties under certain conditions. Solubility is one property that can change when the conditions such as pH, temperature, and/or polymer concentration change. Cloud point is the temperature above which the thermoresponsive smart polymer will change its solubility and form aggregates. What is a “smart” polymer? Poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) is a smart polymer that changes its cloud point when conditions change, such as temperature, pH, polymer concentration, and ionic strength. When combined into a diblock copolymer with poly(ethylene glycol), the newly formed polymer, PEG-PDMAEMA, retains the smart polymer properties of PDMAEMA and acquires properties based on its new diblock structure.
Color poster with text, images, and graphs.
Keywords: PEG-PDMAEMA; Smart polymers; Chemistry; Posters